Pengaruh Pemberian Terapi Musik Klasik Terhadap Tekanan Darah Dan Denyut Jantung Pasien Pasca Operasi Dengan Anestesi Umum Di Rs Dr. Moewardi Surakarta - Pradita, Nunung Arian; , Arina Maliya S.Kep,M.Si.Med; , Arief Wahyudi Jadmiko, S.Kep, Ns (2016)
Homodynamic stability was an important indicator of an ideal anesthetic action and influence the anesthetic management plan. Management of complications of anesthesia in space can be recovered aware of pharmacology and complementary therapies as a companion therapy, where complementary therapies are currently experiencing increased interest and use, one of which is music therapy. This study aims to determine the effect of classical music therapy on blood pressure and heart rate in patients post-surgery with general anesthesia in the hospital Dr. Moewardi Surakarta. This study used a quasi-experimental or quasi-experimental study with pre-test and post-test with control group design. Sample study was 30 patients surgery with general anesthesia in the Hospital Dr. Moewardi Surakarta with accidental sampling technique. The collecting data using bed side monitor and data analysis t-test. The study concluded there was a difference in blood pressure and heart rate of patients after surgery with general anesthesia between classical music therapy groups with no treatment group of classical music. Keywords: blood pressure, heart rate, classical music therapy, after general anesthesia.